Adjusting the Prerelease Gut Microbial Community by Diet Training to Improve the Postrelease Fitness of Captive-Bred Acipenser dabryanus - Yang, Haile; Leng, Xiaoqian; Du, Hao; Luo, Jiang; Wu, Jinping; Wei, Qiwei (Frontiers in Microbiology, 2020)
As one of the most important tool for biodiversity restoration and endangered species conservation, reintroduction has been implemented worldwide. In reintroduction projects, prerelease conditioning could effectively increase postrelease fitness and survival by improving animals’ adaptation to transformation from artificial to natural environments. However, how early-life diet training affects individuals’ adaptation, fitness and survival after release remains largely unknown. We hypothesized that early-life diet training would adjust the host’s gut microbial community, the gut microbial community would influence the host’s diet preference, and the host’s diet preference would impact its adaptation to diet provision transformation and then determine postrelease fitness and survival. To verify this hypothesis, we investigated the growth characteristics and gut microbes of Yangtze sturgeon (Acipenser dabryanus) trained with natural and formula diets at both the prerelease and postrelease stages. The results showed that (1) the gut microbial communities of the individuals trained with a natural diet (i.e., natural diet group) and formula diet (i.e., formula diet group) evolved to the optimal status for their corresponding diet provisions, (2) the individuals in the natural diet group paid a lower cost (i.e., changed their gut microbial communities less) during diet transformation and release into the natural environment than did the individuals in the formula diet group, and (3) the gut microbes in the natural diet group better supported postrelease fitness and survival than did the gut microbes in the formula diet group. The results indicated that better prerelease diet training with more appropriate training diets and times could improve the reintroduction of Yangtze sturgeon by adjusting the prerelease gut microbial community. Because a relationship between diet (preference) and gut microbes is common in animals from insects (such as Drosophila melanogaster) to mammals (such as Homo sapiens), our hypothesis verified by the case study on Yangtze sturgeon applies to other animals. We therefore encourage future studies to identify optimal training diets and times for each species to best adjust its prerelease gut microbial community and then improve its postrelease fitness and survival in reintroduction projects.